The institutional responses to new plant variety protection in China in the context of big data - Yu, Fenglei; Liu, Xiaochang (Frontiers in Plant Science, 2025)
Improving the new plant variety protection system is of great significance for China to complete the transformation of modern agriculture. At present, China has initially built up a new plant variety protection system with the Regulation of the People’s Republic of China on the Protection of New Varieties at its core. However, the arrival of the digital era has brought far-reaching impacts and strong impacts on the traditional breeding industry, and at the same time, it also puts forward more stringent requirements on the existing protection system. Based on this, this paper will mainly use the comparative research method and literature analysis method to analyse the systems adopted by other countries for the protection of new plant varieties, and at the same time examine the shortcomings and deficiencies of the current system in China. On this basis, this paper will focus on how to improve the data application capacity, promote data sharing, establish the three-dimensional protection mechanism, and improve the benefit-sharing mechanism, so as to promote the continuous improvement and upgrading of China’s new plant variety protection system.